The existentialist conception of man: a comparative analysis between Muhammad Iqbal and Jean-Paul Sartre - Nusrat, Zubaida; Abdul Rahim, Adibah (IIUM Press, 2025)
This article examines the existentialist conception of man, as presented in the philosophical and literary works of Muhammad Iqbal and Jean-Paul Sartre, drawing attention to both their similarities and differences. The analysis reveals how both thinkers address human existence, abstraction, freedom, alienation, identity formation and authenticity, reflecting their respective theistic and atheistic ideologies. Iqbal’s concept of man, based on his idea of “Khudi” (selfhood), emphasises self-realisation, creativity, and the development of individuality in line with divine principles, focusing a dynamic vision of human potential and spiritual evolution. Sartre’s view of man, however, centred on the idea that “existence precedes essence,” defines man as devoid of any inherent essence or divine guidance, encouraging to create meaning and identity through the freedom of actions and choices. Despite originating from distinct metaphysical traditions, the two perspectives share a common concern with the existential challenges of self-discovery and the pursuit of meaning in a complex and contradictory world.